Abundance and morphometry of Daphnia lumholtzi in Lake Texoma, OK, USA in 2010-2011 - Beyer, Jessica E; Hambright, K David (Supplement to: Beyer, JE; Hambright, KD (2019): The niche and morphology of the invasive Daphnia lumholtzi in a subtropical reservoir, 20 years after invasion. Journal of Plankton Research, 41(2), 90-100, https://doi.org/10.1093/plankt/fby053, 2019)
In Lake Texoma, OK, USA, we measured the abundance and morphometry of Daphnia lumholtzi. Samples were collected at five pelagic sites (see below for coordinates) over the course of fourteen months (June 2010-July 2011). Zooplankton were collected using vertical tow over the full water column (depth-integrated) with a Wisconsin-type net (350-μm mesh, aperture diameter 10.5 cm). Zooplankton were enumerated and morphology of Daphnia lumholtzi was measured using a dissecting microscope. Water quality parameters, including water temperature (°C), salinity (practical salinity units, PSU), dissolved oxygen (mg L−1), chlorophyll (μg L−1), phycocyanin (proportional to μg L−1), total nitrogen (μM), total phosphorous (μM), native Daphnia spp. density (females L−1) and Secchi depth (m). Water samples for nutrients (nitrogen and phosphorus) were taken as depth integrated samples over the upper 10 m. A Hydrolab sonde was used to measure temperature, salinity, dissolved oxygen, chlorophyll, and phycocyanin at 1-meter intervals over the upper 10 m, then averaged across those depths.